2007
DOI: 10.1007/s10092-007-0129-9
|View full text |Cite
|
Sign up to set email alerts
|

Structured matrix algorithms for inverse scattering on the line

Abstract: In this paper we present an algorithm for the construction of the superoptimal circulant preconditioner for a two-level Toeplitz linear system. The algorithm is fast, in the sense that it operates in FFT time. Numerical results are given to assess its performance when applied to the solution of two-level Toeplitz systems by the conjugate gradient method, compared with the Strang and optimal circulant preconditioners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The governing equations of the 1-D CISP are given by (1) where and are the right-and left-propagating waves, respectively, is the local reflectivity function (LRF) at the position , and is the time variable. We try to find when and , called scattering data, are given.…”
Section: A Discretization Of the 1-d Cispmentioning
confidence: 99%
See 1 more Smart Citation
“…The governing equations of the 1-D CISP are given by (1) where and are the right-and left-propagating waves, respectively, is the local reflectivity function (LRF) at the position , and is the time variable. We try to find when and , called scattering data, are given.…”
Section: A Discretization Of the 1-d Cispmentioning
confidence: 99%
“…The Taylor series for at is given by 1 The normalization factor (NF) is important for energy conservation. However, this NF is a cofactor for all elements of a generator matrix.…”
Section: B Asymptotic Expansionmentioning
confidence: 99%
“…Different numerical approaches to this computationally difficult problem have been developed. We mention the papers of Aktosun and Sacks and Rundell and Sacks restricted to potentials not admitting bound state data, the paper of van der Mee et al in which a discretization scheme for the Gel'fand‐Levitan‐Marchenko equation was developed, and the paper of Altundağ et al where a brief review of existing approaches can be found.…”
Section: Introductionmentioning
confidence: 99%
“…In all of the applications mentioned above, accuracy of the numerical algorithms form a bottleneck either at higher powers in the non-Hermitian class or at reflectivities approaching unity in the Hermitian class. There is a vast amount literature on numerical methods for the solution of the Gelfand-Levitan-Marchenko (GLM) integral equations notable among them are the integral layer-peeling [7], Töplitz inner-bordering [9][10][11] and the Nyström method [12]. From a practical viewpoint, these algorithms work for a large class of problems; however, these methods cannot provide accuracies upto the machine precision with the exception of the method due to Trogdon and Olver [13].…”
Section: Introductionmentioning
confidence: 99%